Identification of a New Type 2M von Willebrand Disease Mutation also at Position 1324 of von Willebrand Factor - Hilbert, L.; Fressinaud, E.; Ribba, A. S.; Meyer, D.; Mazurier, C.; and the INSERM network on molecular abnormalities in von Willebrand disease (Thrombosis and Haemostasis, 2002)
Type 2M von Willebrand disease (VWD) refers to variants with decreased platelet-dependent function that is not associated with the loss of high molecular weight (HMW) von Willebrand factor (VWF) multimers. This category includes the so-called “phenotype B” responsible for inexistent ristocetin-induced but normal botrocetin-induced binding of VWF to platelet glycoprotein Ib. The missense mutation G1324S was identified in the first patient reported to display “phenotype B”.We report here on the identification in four members of a French family of a missense mutation also affecting this glycine residue but changing it into an alanine residue. These individuals are heterozygous for this mutation and two of them display an additional quantitative VWF deficiency resulting from a stop codon at position 2470. After transient transfection in Cos-7 cells, the mutated recombinant protein harbouring the G1324A substitution was shown to exhibit normal multimers and inexistent ristocetin-induced but normal botrocetininduced binding to GPIb, confirming the classification of this new mutation as a type 2M VWD mutation.
Keywords: von Willebrand factor; von Willebrand disease; mutation; recombinant protein; Cos-7 cells